Islamic Religious Education Students’ Perceptions and Experiences in Using Artificial Intelligence for English Grammar Learning - Mukmin Ridoan Simamora; Yuli Kuswandari; Nur Hidayat (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aims to explore Islamic Education students’ experiences of using Artificial Intelligence tools for English grammar learning and to identify the perceived benefits and challenges of AI-assisted grammar learning from the students’ perspectives. Methods – This study employed an exploratory descriptive qualitative design. Data were collected through classroom observations and semi-structured interviews with 20 students who had experience using AI-based tools, such as ChatGPT, Gemini, Perplexity, Grammarly and QuillBot. The data were analyzed using Miles and Huberman’s interactive model. Findings – The findings indicate that students perceived AI as useful for obtaining grammar explanations, checking sentence errors, generating examples, and supporting independent learning. AI was also reported to increase students’ confidence and provide flexible access to learning support. However, students also identified several challenges, including inaccurate or overly general responses, limited contextual understanding, unstable internet access, restricted premium features, and the risk of overdependence.Research Implications – These findings suggest that AI can support grammar learning when used critically and under lecturer guidance. The study should be interpreted as evidence of students’ perceived benefits and challenges rather than direct evidence of improved grammar competence.